2012
DOI: 10.2478/v10152-012-0022-z
|View full text |Cite
|
Sign up to set email alerts
|

The effects of particulate matter air pollution on respiratory health and on the cardiovascular system

Abstract: Particulate matter (PM) is a major component of urban air pollution and hasand also in chronic obstructive pulmonary diseases (COPD) has been observed in developed countries over the last 3 decades (11,12,13,14,15,16). The adverse effect of PM on respiratory health has a quantifiable impact, not only on the morbidity but also on the mortality of respiratory diseases (17, 18). On the other hand the possible association between cardiovascular diseases (CVD) and exposure to airborne PM has only recently been addr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 91 publications
0
14
0
Order By: Relevance
“…Multiple studies confirm that PM 2.5 and PM 10 can affect lung growth and development in children and adolescents, number of medical visits, and hospital emergency admissions due to the asthma, respiratory symptoms, and upper and lower respiratory tract disorders (Brown et al 2013 ; Linares and Diaz 2010 ; Praznikar and Praznikar 2012 ; WHO 2013 ).…”
Section: Health Riskmentioning
confidence: 99%
“…Multiple studies confirm that PM 2.5 and PM 10 can affect lung growth and development in children and adolescents, number of medical visits, and hospital emergency admissions due to the asthma, respiratory symptoms, and upper and lower respiratory tract disorders (Brown et al 2013 ; Linares and Diaz 2010 ; Praznikar and Praznikar 2012 ; WHO 2013 ).…”
Section: Health Riskmentioning
confidence: 99%
“…The first comprises numerous studies of life expectancy gains arising from specific medical interventions and innovations. The second group studies the relationship between risk factors and life expectancy but, given the complexity of this relationship, either the impact of a specific risk factor on different causes of death is investigated ( 3 - 5 ), or different risk factor modifications for a specific disease are observed ( 6 - 7 ). The third group investigate the impact of the major causes of death on life expectancy, often combined with decomposition by age ( 8 - 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…The Organization for Economic Cooperation and Development (OECD) evaluated in its outlook (OECD, 2012) that PM pollution will be the primary cause of deaths of African population by 2050, in comparison to hazardous water and poor hygiene. Pražnikar and Pražnikar (2012) comprehensively addressed in their review several epidemiological studies throughout the world; they reported a strong association between the PM concentrations and respiratory morbidity, cardiovascular morbidity and total mortality.…”
Section: Current Status and Challenges 721 Health Impacts Of Particulate Matter (I) Overview Of The Health Impacts Of Particulate Matter mentioning
confidence: 99%